Respuesta :
-18 = 117/(p-9)
(p-9)(-18) = 117
p-9 = 117/-18
p = (117/-18) +9
p = 2.5
(p-9)(-18) = 117
p-9 = 117/-18
p = (117/-18) +9
p = 2.5
Hey there!
So here are the steps you need to follow to get the answer!
-18 = 117/(p - 9)
-18(p - 9) = 117 -----> multiply "(p - 9)" on both sides
-18p + 162 = 117 ------> distribute the "-18"
-18p = -45 ------> subtract "162" on both sides
p = 2.5 ------> divide "-18" on both sides
I hope this helps! :D
Please vote me for Brainliest if there is a second answer!!!
So here are the steps you need to follow to get the answer!
-18 = 117/(p - 9)
-18(p - 9) = 117 -----> multiply "(p - 9)" on both sides
-18p + 162 = 117 ------> distribute the "-18"
-18p = -45 ------> subtract "162" on both sides
p = 2.5 ------> divide "-18" on both sides
I hope this helps! :D
Please vote me for Brainliest if there is a second answer!!!